(untitled) (Research, Society and Development, 2020)
A study was conducted in order to estimate the sodium requirements of Japanese laying quail (Coturnix coturnix japonica). In this study, we used 280 Japanese quails at 128 days of age, with an average weight of 9 ± 5.2 g, and an egg production rate of 82.3 ± 0.94%. An experimental design methodology was employed, completely randomized with five treatments and seven replications. Each replicate consisted of eight quails, with a total of thirty-five experimental units. The experimental diets were based on corn and soybean meal, and contained five different levels of sodium (0.08%, 0.12%, 0.16%, 0.20% and 0.24%). The diets were isocaloric and contained equal concentrations of amino acids, with an electrolyte balance of 250 mEq/kg. The parameters we evaluated were feed intake (g/quail/day); egg production per quail per day (%); egg weight (g); egg mass (g/quail/day); and feed conversion by egg mass (kg/kg) and per dozen eggs (kg/dz). In addition, we evaluated the composition of the eggs in terms of the absolute (g) and relative (%) mass of the yolk, albumen and eggshell. We also measured the body weight variation (g) and viability (%) of the quails. There were no significant effects (p>0.05) on the described parameters. No nutritional disorders occurred related to the level of inclusion of sodium in the diets. The inclusion of 0.08% sodium in the diet of laying Japanese quails was satisfactory to maintain egg production and quality without losses in feed intake or feed conversion.